2021
DOI: 10.1101/2021.12.07.471561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aedes koreicus, a vector on the rise: pan-European genetic patterns, mitochondrial and draft genome sequencing

Abstract: BackgroundThe mosquito Aedes koreicus (Edwards, 1917) is a recent invader on the European continent that was introduced to several new places since its first detection in 2008. Compared to other exotic Aedes mosquitoes with public health significance that invaded Europe during the last decades, this species’ biology, behavior, and dispersal patterns were poorly investigated to date.Methodology/Principal FindingsTo understand the species’ population relationships and dispersal patterns within Europe, a fragment… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…After its first detection in Belgium in 2008 (Versteirt et al, 2012), the mosquito Aedes koreicus, commonly known as the invasive Korean bush mosquito, has invaded and established in several states in Europe and European neighbouring countries (ECDC, 2022). In some areas, such as Italy, the species is currently expanding its distribution (Gradoni et al, 2021;Negri et al, 2021;Arnoldi et al, 2022), but in others, such as Germany, it has shown a relatively low tendency to spread despite suspected repeated introductions (Hohmeister et al, 2021;Kurucz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…After its first detection in Belgium in 2008 (Versteirt et al, 2012), the mosquito Aedes koreicus, commonly known as the invasive Korean bush mosquito, has invaded and established in several states in Europe and European neighbouring countries (ECDC, 2022). In some areas, such as Italy, the species is currently expanding its distribution (Gradoni et al, 2021;Negri et al, 2021;Arnoldi et al, 2022), but in others, such as Germany, it has shown a relatively low tendency to spread despite suspected repeated introductions (Hohmeister et al, 2021;Kurucz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%